Pembiayaan Pembangunan Tanah Wakaf di Negeri Johor - Nor Azlan, Nur Alya Sabreena; Mohsen, Masfaliza; Kasim, Rozilah; Omar, Ismail (Research in Management of Technology and Business, 2020)
Waqf is one of the most important Islamic institutions that promoting the economic development and well-being of the Ummah. Johor has a vast waqf land, but not all of it can be developed, let alone abandoned. The Johor Islamic Religious Council (MAIJ) acts to develop potentially viable land. However, the financing funds for waqf land development are limited. This situation has caused difficulties for MAIJ to fully utilize the land primarily in terms of rates and rental values. A productive waqf land development begins with the financing of the waqf land itself. Hence, sources of funding for waqf land need to be reviewed and revised as a paradigm shift in boosting the Islamic economy. The purpose of this study is to investigate the types of financing used by MAIJ for the development of waqf land in Johor and the financing problems faced by MAIJ. This study used a qualitative approach in which data were obtained through an interview with the MAIJ waqf management. The scope of this study is in Johor. Data obtained were analyzed by using thematic network analysis. The findings show the types of financing sources utilized by MAIJ and the financing problems encountered in waqf land development in Johor. In conclusion, this study is expected to serve as a guide for MAIJ to improve the land management system and waqf funding.